Cheguei, e agora? a dimensão afetiva na inserção do estudante estrangeiro no ambiente universitário: um olhar walloniano - Silva, Herbert Souza da (2014)
This work, developed through a qualitative research, with an exploratory approach, discusses the affective dimension in the insertion of foreign students in the university environment from the perspective of Wallon s theory, aiming to identify which feelings and emotions are manifested by foreign students and what extent the role of the environment and of the other influence on the integration process of these students into the university. The work is structured beginning with a discussion on the issue of globalization, noting that the internationalization of education is a necessity to keep up with the global issues and forming individuals capable of acting in this context. Subsequently, we present the extension course of PUC-SP Brazilian Portuguese: Language and Culture, locus of the human subject of the research. Then we discuss the affective dimension in the integration process of foreign student from the theory of Henri Wallon, considering the concepts of the role of the environment and of the other, and the integration of functional sets. The methodology consists of three techniques for data collection: observation conducted with a group of 47 international students at the beginning of the course in 2013, survey applied to 55 foreign students in 2014 and semi-structured interviews conducted with two foreign students. Based on the results presented, it was possible to identify, in this particular context, a diversity of feelings experienced by students, both nice shades as negative shades. It was clear, too, that the role of the environment and of the other influence on the insertion process of foreign student and may offer possibilities for their development as also limitations. The interaction with the environment and with other shows as essential to the transformation of the student, providing their inclusion and the learning process